Gaya Bahasa Puisi Peserta Didik Tingkat Sekolah Menengah (Studi Kasus SMPIT Raudhatul Jannah, Cilegon Banten): The Study of Language and Literature (locution) of Junior High School Students (Case Study of SMPIT Raudhatul Jannah, Cilegon Banten) - Nur Seha; Rukmini Rukmini (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
This study aimed to describe the locution that is used by the students of SMPIT Raudhatul Jannah, Cilegon, Banten. This study used Altenbernd’s theory in Pradopo (2014) about figurative language. The data source is the result of transforming a short movie into a poem. The data collecting techniques are descriptive qualitative method and the mix-method field technique (interviewing and recording) and also literature review. The data analysis is done at word level and the bundled of words. Furthermore, the interpretation is used to get the students’ comprehension and the description of locution is used on the students’ poems that preceded by airing five short films in front of the students. The conclusion showed that there were simile found in seven (7) poems, metaphore in six (6) poems, epic comparison only in two (2) poems, allegory in six (6) poems, personification found in twenty eight (28) poems, metonimia found in eighteen poems, and sinekdoki found in fifteen (15) poems. Besides that, there are fifteen poems that did not contain of those seven figurative language or locution based on Altenbernd’s theories.